Resilience and Hope: Exploring Immigrant and Refugee Youth Experiences through Community-based Arts Practice - McLeod, Heather; Lewis, Leah B.; Li, Xuemei (Engaged Scholar Journal, 2020)
Community-based arts practice is programming that informs and fosters essential components of well-being and belonging, including resilience, community attachment via interpersonal connection and exchange as preventive to mental health stressors. Our Art Hive is in a centre-city high school with immigrant and refugee youth in St. John’s Newfoundland, where newcomers often face an insider/outsider dynamic of disconnection. The pop-up Art Hive is a publicly accessible and community-located art-making space grounded in Adlerian theory, collaborative community development, feminist thought, and social justice. Through a community-situated arts-based participatory process, we sought emergent themes. An earlier phase of our collaborative project involved visual art-making and exploring experiences of inclusion and belonging. A second phase of the project included some of the same youth and new members, adding local students invited by the immigrant and refugee youth. This phase explored resilience and hope as a feature of well-being and functioning and as having a relationship with immigrant and refugee youth experiences in smaller Canadian centres. The Art Hive, a form of community art therapy practice, is structured along seven social parameters: focus on intentional art-making, no critical commentary (positive or negative), non-evaluative in nature, no forced participation, witnessing, sharing, and participatory involvement of facilitators. The participant-planned and hosted final exhibit contributed to learning, sharing, and group cohesiveness. A focus group generated data on how the Art Hive informs cultural experiences and feelings of hope.